The Effect of Kinesiotaping and Nerve Mobilization on Reduction of Doms - Sari, Suriani; Daryanto, Zusyah Porja (INSPIREE: Indonesian Sport Innovation Review, 2023)
The purpose of the study. This research aims to determine the effectiveness of giving ice massage after training in reducing the occurrence of DOMS. Method. The research design used was the Post Test Only With Control Group Design research method, the sample size was 20 students. The sample was divided into 2 groups, group I was the treatment group (kinesiotaping and nerve mobilization) and group 2 was the control group (without kinesiotaping and nerve mobilization). Subjects performed maximal contractions and exceeded the training load. Subjects performed 75 contractions and divided into 3 training sets. Each set of 25 contractions with a load of 18 kg. After training, the treatment group was given kinesiotaping and nerve mobilization, kinesiotaping and nerve mobilization were given after 30 minutes of training in the treatment group, then the control group was not given kinesiotaping and nerve mobilization. DOMS measurements were carried out using the talaq scale, where measurements were carried out after kinesiotaping and nerve mobilization were given and without kinesiotaping and nerve mobilization. Result. For the non-kinesiotaping and nerve mobilization variables, the probability obtained was p 0.010 < 0.05. The difference between the treatment group and the control group using the Mann-Whitney test obtained a probability of 0.026 < 0.05. Conclusion. By looking at the results of the data obtained, it can be concluded that providing kinesiotaping and nerve mobilization as quickly as possible can reduce the risk of DOMS, whereas without providing kinesiotaping and nerve mobilization cannot reduce the risk of DOMS. To avoid wider damage from the effects of overloaded training, giving ice massage early will help reduce the risk of DOMS.